PENGAYAAN MEDIA KULTUR Chlorella sp. MENGGUNAKAN EKSTRAK LIMBAH TAOGE DENGAN PENAMBAHAN ECO ENZYME - Fauzana, Noor Arida; Rukmini, Rukmini; Ansyari, Pahmi; Slamat, Slamat; Redha, El; Akbar, Junius; Siswanto, Siswanto; Sholihah, Intan Nur (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
Chlorella sp is a type of natural feed that is given to the fish larvae. Chlorella sp. culture requires fertilizer that serves as a food source to stimulate its growth. Fertilization for Chlorela culture media can utilize bean sprout waste because it is rich in element of N and enriched with the addition of eco enzymes. Eco enzyme is the result of fermentation of organic waste such as fruit waste, sugar and water which produces enzymes that help in the process of accelerating the overhaul of organic matter. This study aims to analyze the growth of chlorella with the addition of eco enzyme to the culture media of bean sprout waste extract. The research was carried out by an experimental method using a Complete Random Design with 4 treatments and 3 replicates, namely Chlorella sp. culture on bean sprout waste extract media with the addition of eco enzyme as much as 0.5,10,15 mL per liter for 15 days. The results showed that the treatment of bean sprout waste extract culture media with the addition of eco enzyme as much as 10 mL/L. gave the population of Chlorella sp. the highest was 106.6×106 cells/mL with an average growth rate of 21 ×106 cells/mL. The average growth rate of Chlorella sp. in each treatment ranged from 17% – 29%. The growth curve of Chlorella sp. during the 15-day culture showed that the treatment without the addition of eco enzyme in the bean sprout waste extract medium experienced a longer adaptation phase than the others. The quality of water and nutrients during the culture is in a good range for the growth of Chlorella sp. Further research can evaluate the use of eco enzymes for the growth of other microalgae and the and using different organic waste extracts.